2013
DOI: 10.1038/srep01209
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Assisted Growth of t-Te Nanotubes and their Controlled Photo-induced Unzipping to ultrathin core-Te/sheath-TeO2 Nanowires

Abstract: One dimensional (1D) nanostructures of semiconducting oxides and elemental chalcogens culminate over the last decade in nanotechnology owing to their unique properties exploitable in several applications sectors. Whereas several synthetic strategies have been established for rational design of 1D materials using solution chemistry and high temperature evaporation methods, much less attention has been given to the laser-assisted growth of hybrid nanostructures. Here, we present a laser-assisted method for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…The hetero-interface nucleation made Te atom more easily to deposit on the surface of the template. The most active site for Te atom is along \0001[ direction due to the driving force of free energy [37][38][39]. In our experiment, the guiding effect of the surfactant template is not strong enough to change its growth direction, so Te atom is more easy to grow on the axial direction along \0001[.…”
Section: Resultsmentioning
confidence: 92%
“…The hetero-interface nucleation made Te atom more easily to deposit on the surface of the template. The most active site for Te atom is along \0001[ direction due to the driving force of free energy [37][38][39]. In our experiment, the guiding effect of the surfactant template is not strong enough to change its growth direction, so Te atom is more easy to grow on the axial direction along \0001[.…”
Section: Resultsmentioning
confidence: 92%
“…Visible light illumination of t-Te surfaces results in a variety of nano-structuring phenomena as have been reported elsewhere. 18 The formation of t-Te nanotubes that are disintegrated into t-Te/a-TeO 2 core/sheath nanowires, such as that shown in the TEM Fig. 2(a), takes place at high power densities.…”
Section: Resultsmentioning
confidence: 98%
“…5 In the present article, we report the results of photoinduced processing of crystalline trigonal Te (t-Te) using cw lasers operating at the visible wavelength spectral range as recently demonstrated elsewhere. 18 It is shown that irradiation causes photo-oxidation and amorphization of t-Te. The time-dependent kinetics of these processes is explored as a function of laser fluence.…”
Section: Introductionmentioning
confidence: 99%
“…In the inset , the maximum photocurrent obtained for each cycle, I phmax, is plotted as a function of light power density F According to refs. [6,23,28], the origin of photoconduction in this material may be attributed to the coexistence of Te and TeO2 phases due to the partial oxidation of Te grains as demonstrated by XRD analysis.…”
Section: Fig 10mentioning
confidence: 99%
“…For example, Rao et al [14] reported controlled synthesis of Te nanorods, nanowires, nanobelts, and related structures by the disproportionation of NaHTe in different solvents, Xia et al [15,16] prepared uniform Te nanowires and nanotubes through the reduction of H6TeO6 by N2H4H2O or ethylene glycol in refluxing process, and Qian's group produced a series of 1D Te nanostructures including nanowires, nanobelts, and nanotubes via hydrothermal synthesis [17][18][19][20]. Recently, Zhu et al [21] presented an ultrasonic-assisted solution-phase approach for the fabrication of tellurium bundles of nanowhiskers, Sen et al [22] synthesized Te nanostructures by physical vapor deposition, and Vasileiadis et al demonstrated that a controlled fabrication of Te nanotubes can be carried out by irradiating bulk elemental Te with continuous wave lasers emitting in visible range for short exposure time [23].…”
Section: Introductionmentioning
confidence: 99%